2017
DOI: 10.1016/j.bbrc.2017.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa increases MUC1 expression in macrophages through the TLR4-p38 pathway

Abstract: Alveolar macrophages (AMs) play a critical role in the clearance of Pseudomonas aeruginosa (Pa) from the airways. However, hyper-activation of macrophages can impair bacterial clearance and contribute to morbidity and mortality. MUC1 mucin is a membrane-tethered, high molecular mass glycoprotein expressed on the apical surface of mucosal epithelial cells and some hematopoietic cells, including macrophages, where it counter-regulates inflammation. We recently reported that Pa up-regulates the expression of MUC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Given that P. aeruginosa binds to MUC1/Muc1 through its flagella [ 61 ], it is possible that this difference in phagocytosis may be related, in part, to the fact that S. pneumoniae is non-flagellated. We next investigated the mechanism through which P. aeruginosa regulates MUC1 expression by macrophages [ 87 ]. P. aeruginosa stimulation of human macrophages increased MUC1 expression both at the transcriptional and protein levels in a dose-dependent manner.…”
Section: Additional Role Of Airway Macrophages In the Anti-inflammentioning
confidence: 99%
“…Given that P. aeruginosa binds to MUC1/Muc1 through its flagella [ 61 ], it is possible that this difference in phagocytosis may be related, in part, to the fact that S. pneumoniae is non-flagellated. We next investigated the mechanism through which P. aeruginosa regulates MUC1 expression by macrophages [ 87 ]. P. aeruginosa stimulation of human macrophages increased MUC1 expression both at the transcriptional and protein levels in a dose-dependent manner.…”
Section: Additional Role Of Airway Macrophages In the Anti-inflammentioning
confidence: 99%
“…Mechanistically, the results of the present study identified TLR4 as a direct target of miR-23a-5p in RASFs. TLR4, as a member of the TLR family, is widely distributed in various cells, such as T cells, B cells, lung macrophages, adipocytes and intestinal epithelial cells (52)(53)(54)(55). The extracellular domain of the TLR4 structure can combine with the myeloid differentiation-2/CD14 complex, identify pathogen-associated molecular patterns and eventually activate NF-κB signaling (56).…”
Section: Discussionmentioning
confidence: 99%
“…In primary human alveolar macrophages isolated from the BAL of healthy subjects and human monocytic cell line (THP-1 cells), P. aeruginosa infection significantly increased MUC1 expression compared to uninfected cells [57]. Macrophages recognize this bacterium through TLR4 and the stimulation of the THP-1 cells with P. aeruginosa increased MUC1 protein levels 5.4-fold, whereas pre-treatment with the viral inhibitory peptide of TLR4 significantly reduced P. aeruginosa-induced MUC1 RNA levels down to 1.3-fold [58]. Furthermore, P. aeruginosa infection of human NCI-H292 airway epithelial cells increased MUC5AC mRNA and protein [59].…”
Section: P Aeruginosamentioning
confidence: 98%